2020
DOI: 10.3390/ijms21239114
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytoma: A Hormone-Sensitive Tumor?

Abstract: Astrocytomas and, in particular, their most severe form, glioblastoma, are the most aggressive primary brain tumors and those with the poorest vital prognosis. Standard treatment only slightly improves patient survival. Therefore, new therapies are needed. Very few risk factors have been clearly identified but many epidemiological studies have reported a higher incidence in men than women with a sex ratio of 1:4. Based on these observations, it has been proposed that the neurosteroids and especially the estrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 137 publications
0
43
1
Order By: Relevance
“…A debated topic without a definitive answer today is the role of hormones [26][27][28][29][30]. Interestingly, we did note a small but significant difference related to age at diagnostic surgery, with female patients generally being older, which could suggest a role for hormonal factors.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…A debated topic without a definitive answer today is the role of hormones [26][27][28][29][30]. Interestingly, we did note a small but significant difference related to age at diagnostic surgery, with female patients generally being older, which could suggest a role for hormonal factors.…”
Section: Discussionmentioning
confidence: 60%
“…Estrogen is found at higher concentrations in female brains, where it binds to nuclear or membrane receptors. This leads to many different and complex effects that could contribute to the sex disparity [26]. While some studies have found a correlation of glioma incidence to exogenous hormone treatment, such as oral contraceptives or hormone replacement therapy, others have not [28,30].…”
Section: Discussionmentioning
confidence: 99%
“…Although little is known about GBM etiology, numerous sources indicate that women are 50% less likely to develop a GBM than men and respond better to standard treatment [ 7 , 8 ]. Thus, the circulating estrogens produced by the gonads or those synthetized locally in the brain could play a protective role against gliomagenesis [ 9 ]. This hypothesis is supported by observations linking exogenous hormone intake to a statistical increase in survival [ 7 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Astrocytomas (AcTs), the most common gliomas, are tumors that originate in astrocytes, a type of glial cells star-shaped and localized in the cerebrum [ 172 ]. In adult individuals, AcTs are additionally the most common brain tumors, the most aggressive primary brain tumors, and those with the poorest vital prognosis [ 173 ].…”
Section: Primary Brain Tumorsmentioning
confidence: 99%